Advancing Digital Financial Inclusion in ASEAN : Policy and Regulatory Enablers - Trujillo, Veronica (World Bank, Washington, DC, 2018)
This report provides a cross-country overview of the policy and regulatory framework for digital financial services (DFS) in Association of Southeast Asian Nations (ASEAN) countries from a financial inclusion perspective. It was carried out at the request of the ASEAN Working Committee on Financial Inclusion (WC-FINC). The analysis is based on a regulatory survey conducted by the ASEAN WC-FINC, supplementary interviews with relevant regulatory authorities, and a literature review. For the purposes of this study, DFS consists of the range of services accessed and delivered through digital channels, including payments, savings, and credits (AFI 2015). The analysis uses as a methodological framework the foundations and catalytic pillars proposed by the Payment Aspects of Financial Inclusion report, or PAFI (World Bank 2016). This framework was adjusted to consider DFS more broadly and to focus on policies and regulations only.